2016
DOI: 10.2174/1874312901610010071
|View full text |Cite
|
Sign up to set email alerts
|

The Avise Lupus Test and Cell-bound Complement Activation Products Aid the Diagnosis of Systemic Lupus Erythematosus

Abstract: Background:Systemic lupus erythematosus (SLE) is a multifaceted disease, and its diagnosis may be challenging. A blood test for the diagnosis of SLE, the Avise Lupus test, has been recently commercialized and validated in clinical studies.Objectives:To evaluate the use of the Avise Lupus test by community rheumatologists.Methods:The study is a longitudinal, case-control, retrospective review of medical charts. Cases had a positive test result, and controls had a negative result; all patients were anti-nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 31 publications
2
15
1
Order By: Relevance
“…Our study represents an advance in research regarding the clinical utility of the AVISE CTD test. While previous studies have shown that the test improves the sensitivity and specificity of diagnosing SLE in cases versus controls,15 16 we have demonstrated that AVISE positivity can not only predict development of SLE within a 2-year interval, but also with equal or greater specificity and greater sensitivity than traditional biomarkers. AVISE positivity at baseline in this cohort also demonstrated a 10.7-fold increased OR for a confirmed SLE diagnosis at 2 years.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Our study represents an advance in research regarding the clinical utility of the AVISE CTD test. While previous studies have shown that the test improves the sensitivity and specificity of diagnosing SLE in cases versus controls,15 16 we have demonstrated that AVISE positivity can not only predict development of SLE within a 2-year interval, but also with equal or greater specificity and greater sensitivity than traditional biomarkers. AVISE positivity at baseline in this cohort also demonstrated a 10.7-fold increased OR for a confirmed SLE diagnosis at 2 years.…”
Section: Discussioncontrasting
confidence: 56%
“…The AVISE CTD test has been demonstrated to aid in differentiation of SLE diagnosis from other CTDs and FM 15 16. We present here the first study to evaluate its clinical utility in a real-world cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, MAP and CB-CAPs consistently outperform serum complement levels for SLE diagnosis. A case–control, retrospective review of medical charts also suggested the clinical utility of MAP/CB-CAPs laboratory testing in assisting rheumatologists in real-world practice 11. However, prospective data comparing standard diagnosis laboratory testing (SDLT) to MAP/CB-CAPs laboratory testing is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…While objective measures (SLICC criteria) were correlated with AVISE, there is no assurance that knowledge of the test did not affect the scoring. This is hinted at by other studies showing that a patient with a positive AVISE test is more likely to be diagnosed with SLE regardless of the number of criteria met,18 and that rheumatologists are less likely to diagnose lupus in a patient with a negative AVISE test, regardless of other features 19…”
mentioning
confidence: 91%